Too dry and too cold for mould germination in New Zealand dwellings?. (6th December 2007) - Boulic, Mikael; Phipps, Robyn; Cunningham, Malcolm; Cleland, Don; , Par Fjallstrom
The indoor climate was investigated in 25 dwellings during the winter of 2005, in the Hutt Valley region (Greater Wellington, New Zealand). A temperature/relative humidity sensor and a fungal detector were attached to the indoor side of the external wall in the living room and in the asthmatic child's bedroom for an average period of 42 days. Germinated spores in the fungal detector were counted under a microscope. Only 2% of the Aspergillus penicillioides, 6% of the Eurotium herbariorum and 22% of the Alternaria alternata inclusions, showed germination of spores. Severe visible mould contamination was observed in only 12% of rooms studied. Consistent with these results, the measured average temperature of 16.7°C ± 0.2°C and relative humidity of 63% ± 1% were lower than normally considered necessary for significant mould development. To confirm these results, the experiment will be repeated in the same dwellings during the winter of 2006.